Detection of human adenovirus 40/41 among children with some hematological disorders - Ali, Alyaa Younis; Hussein, Areej Atiyah; Mahmood, Najdat Shukur (Journal of Ideas in Health, 2019)
Background: Different parts of the world are witnessing a significant increase in the prevalence of human adenoviruses (HAdVs) diarrhea among children. This study aimed to assess the prevalence rate of HAdVs type 40 and type 41 (40/41) infections in children with diarrhea and to assess the relationship between viral infection and different socio-demographic and clinical parameters. Methods: A cross-sectional study was recruited to analyze a convenient sample of children presented with diarrhea. Data was collected from 8th August 2018 till 6th July 2019 at Al-Batool teaching hospital for gynecology and pediatrics in Baquba city, Center of hematology in Baquba city, and the Central teaching hospital of pediatric in Baghdad. Depending on the clinical examination, patients categorized into four groups; Group I with acute diarrhea, Group II with iron deficiency anemia and diarrhea, Group III with thalassemia and diarrhea, and Group IV with leukemia and diarrhea. Each patient gave one stool sample stored in a deep freeze at -20 ̊C for further analysis. Enzyme-linked immunosorbent assay and immunochromatographic test used to test the samples. Results: A total of 184 children aged one month to fifteen years have been included in this study. More than half (97, 52.7%) of children were males. The prevalence rate of HAdVs 40/41 was 4.34%. Patients in the age group ranged from one month to five years, G IV (leukemia and diarrhea), male gender, low educated mothers, and those who changed to spoon feeder are more likely to have a high prevalence of diarrhea due to HAdVs 40/41. The most top clinical sign was fever (7, 87.5%), and the lowest was the loss weight (1, 12.5%), however vomiting, abdominal pain, and dehydration seen among at least three cases. Conclusion: Human adenovirus 40/41 appeared to play a significant role causing acute gastroenteritis among children with leukemia and less than five years old.